Drug Resistance of Mycobacterium tuberculosis Based on Whole-Genome Sequencing in the Yi Ethnic Group, Sichuan Province, China - Wenfeng Gao; Xiaoru Chen; Liang Yao; Jing Li; Yuan Gao; Ting Li; Yunkui Li; Weina Wang; Shu Zhang; Jinge He (Journal of Immunology Research)
This study investigated drug-resistant tuberculosis (DR-TB) in the Yi ethnic group. The study was designed to identify risk factors for DR-TB and its relationship with HIV/AIDS. To establish the resistance to antituberculosis drugs, whole-genome sequencing (WGS) was performed using culture-positive Mycobacterium tuberculosis samples collected from people of the Yi ethnic group from March 2019 to March 2021. Baseline characteristics were obtained from China’s tuberculosis surveillance system. A total of 116 M. tuberculosis strains were included in the final analysis. Lineage 2.2 (75.86%) was the dominant sublineage, followed by lineage 4.5 (18.97%) and lineage 4.4 (5.17%). The rates of rifampicin-resistant (RR-TB), multidrug-resistant (MDR-TB), and preextensively drug-resistant TB (pre-XDR-TB) were 18.97%, 10.34%, and 6.03%, respectively. Drug-resistant strains were not found in the elderly (age≥65 years). The proportions of RR/MDR-TB and pre-XDR-TB cases among re-treatment patients were higher than those among new patients (χ2=12.155, P=0.003; χ2=22.495, P=0.001, respectively). The pre-XDR-TB case proportions were higher among female patients than among males and higher among referred patients (χ2=5.456, P=0.032; χ2=15.134, P=0.002, respectively). The rates of RR/MDR-TB and pre-XDR-TB did not differ appreciably among groups with different HIV infection statuses nor lineage populations. DR-TB poses a serious challenge to the Yi ethnic group. Re-treatment patients, women, and referred patients were at high risk of MDR/RR-TB or pre-XDR-TB while HIV and lineage 2 had negligible association with drug resistance. Whole-genome sequencing should be used to guide the design of treatment regimens and to tailor public interventions.